Sikap Mahasiswa Terhadap Kebijakan Kampus Bebas Asap Rokok di Universitas Muhammadiyah Yogyakarta - Yudan Harry Sandika; Ema Waliyanti (IJNP (Indonesian Journal of Nursing Practices), 2016)
Smoking is one of the problems in society that is diicult to be resolved. In 2011, 6 million deaths each year are caused by smoking. The number of smokers in Indonesia continues to grow which is dominated by the age of 15 years and above. To overcome these problems, the government issued a policy of banning smoking in the learning process places. UMY is one of the places that have already implemented smoke-free campus since 2011, however there are people who still smoke in the campus.The purpose of this study was to determine how the students’ attitude of Universitas Muhammadiyah Yogyakarta toward a smoke-free campus policy. This studywasaqualitativeresearchwithphenomenological approach. The data was taken using the disccusion focus groups, depth interviews and observation. Participants in this study were determined by purposive sampling which were 20 participants consisting of students and campus employees in UMY. The validity of the data in this study was done by using triangulation, triangulation methods and peer debrieing. Data analysis by using the soft ware open code version 4.2. The results indicated that the students who were active smokers agreed and disagreed on KBBR, nevertheless there are diferences in attitudes related to compliance with these rules. Students who were active smokers who agreed to KBBR supported and there were students who did not support the KBBR. But students who were active smokers that did not agree to KBBR did not support the implementation of KBBR on campus. Unlike the students who were active smokers, passive smokers students all agreed and supported KBBR in UMY. By that attitude, UMY needs to increase their knowledge and socialization of KBBR to the students, therefore the students are able to increase the positive attitude towards KBBR in order to create a clean and smoke-free campus.Keywords: Attitude, KBBR, UMY